Mpox: Awareness, knowledge and information channels used by individuals accessing a sexually transmitted infections Helpline - Gallo, Pietro; Galea, Norman; Colucci, Anna; Valli, Rudi; Schwarz, Matteo; Fanales Belasio, Emanuele; D'Ari, Alfredo; Furiozzi, Francesca; Caraglia, Anna; Dalla Torre, Rosa; D'Agostini, Anna (Annali di Igiene Medicina Preventiva e di Comunità, 2024)
Background. Up until recently, monkeypox (mpox) was considered to be a rare zoonotic infection restricted to Central and West Africa. However, in July 2022, the World Health Organization declared mpox to be a public health emergency of international concern, after there were several outbreaks in non-endemic countries. This study assessed the information channels used by individuals accessing the “Telefono Verde AIDS e Infezioni Sessualmente Trasmesse” of Istituto Superiore di Sanità (National Institute of Health in Italy) with regard to mpox. We also evaluated their awareness, and knowledge about mpox focusing on transmission and prevention. Methods. This is a cross-sectional study conducted on “Telefono Verde AIDS e Infezioni Sessualmente Trasmesse” users, between January and April 2023. The target population was helpline users who were older than 18 years of age, and were phoning the service for the first time (i.e. who have not phoned in the last 12 months). Participants were interviewed using a questionnaire containing 19 questions filled by the interviewer. Collected data were analysed through descriptive statistics, and significance testing. Results. From January to April 2023, “Telefono Verde AIDS e Infezioni Sessualmente Trasmesse” received 2,389 phone calls, 216 of which participated in this study. Most of these were male (85.2%; n=186), single (79.2%; n=171) and in employment (72.2%; n=156). Awareness about mpox was high (71.3%; n=154), with the central and south/islands regional areas having the highest percentage of participants who heard about the virus (84.3%; n=43 vs 72.4%; n=42; p=0.078). Television was the most frequently mentioned source of information about mpox by participants (63%; n=97; p<0.001). This medium was also the most preferred source of information about mpox (39%; n=60; p=0.109). The majority of participants stated that they did not know what mpox is (67.6%; n=146), and less than half knew that it is preventable (42.4%; n=89). Of those who stated that mpox is a preventable illness, less than half knew about the existence of a vaccine (44.9%; n=40; p<0.001).